DISKURSUS ILMU HADITS: URGENSI MEMAHAMI ASBAB AL-WURUD AL-HADITS - Ilzam Hubby Dzikrillah Alfani (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
This paper discusses Asbab Al-Wurud Al-Hadith as one of the branches of hadith science. This paper uses a qualitative approach by applying the content analysis method, while the method used by the author is thematic. This type of research is a library study or (library research) which seeks to gather power from various literatures related to the theme of discussion. This paper tries to conduct historical studies, especially in the field of Hadith Science by elaborating on Asbab Al-Wurud Al-Hadith. This discussion concludes Asbab Al-Wurud Al-Hadith as one of the branches of hadith science that must be studied especially by hadith study activists, this aims to get a comprehensive understanding of each hadith studied.